1965
DOI: 10.4141/cjps65-111
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Sawfly Reaction and Stem Solidness in Spring Wheat Crosses: Stem Solidness

Abstract: ABS|IRACTInheritance of stem solidness was studied in populations of F, and Br-lines from the Red Bobs X C.T. 715 and Redman X S-61t (Triticum desti'uum L.) -crosses and backcrosses. Th" data supported the hypothesis that the varieties in each cross differed by four genes for stem solidness. In both crosse,s, one gene exeiied a maior'influenc"e in that its allele for hollowness in the homozygous ;;;diti.; *"6 .pirt"ti" to the other three genes. The other three genes within each cross wer'e similar in their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The use of solid-stem, sawfly-resistant wheat varieties has long been the most effective management tool against Cephus cinctus Norton in North America. While stem solidness is genetically controlled (McKenzie, 1964), environmental and management practices in North America can affect its expression in the field (Luginbill & McNeal, 1954;McNeal et al, 1959;O'Keefe et al, 1960;DePauw & Read, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The use of solid-stem, sawfly-resistant wheat varieties has long been the most effective management tool against Cephus cinctus Norton in North America. While stem solidness is genetically controlled (McKenzie, 1964), environmental and management practices in North America can affect its expression in the field (Luginbill & McNeal, 1954;McNeal et al, 1959;O'Keefe et al, 1960;DePauw & Read, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, parasitoids that kill WSS larvae in the stem reduce WSS stem cutting in susceptible cultivars (Morrill, 1997). High heritability of the solid stem trait and the high correlation between degree of stem solidness and resistance to stem cutting has compelled breeders to use solid stems as a proxy for resistance (McKenzie, 1965).…”
mentioning
confidence: 99%
“…Early genetic analyses suggested the degree of stem solidness was controlled by a single major gene and several minor genes (McKenzie, 1965). Cook et al (2004) reported a single quantitative trait locus (QTL) on chromosome 3BL , named Qss.msub‐3BL , that controlled 76% of the total variation for stem solidness in a recombinant inbred line (RIL) population derived from a cross between solid and hollow stem hexaploid parents (Cook et al, 2004).…”
mentioning
confidence: 99%
“…Cutting by wheat stem sawfly (% incidence) was recorded in those environments where significant infestation by the pest was documented. Stem solidness was determined in selected environments using five stems per plot, sampled randomly near crop maturity using a method like that reported by McKenzie (1965). Five internodes per stem were cross‐sectionally cut and visually rated on a semi‐quantitative scale of 1–5, where 1 designates a hollow (normal) stem and 5 designates a solid stem.…”
Section: Methodsmentioning
confidence: 99%